Sex and glucostatic hormone levels in sportswomen after maximal exercise - Szepanowska, E.; Rychlewski, T.; Wielinski, D.; Hackney, A. C. (Education. Physical training. Sport, 1999)
The purpose of this study was to describe and characterize the hormonal responses of young women athletes to maximal exercise. Two diverse athletic groups were studied, team handball players (n=11) and synchronized swimmers (n=10). All subjects had their physical characteristics assessed using standardized procedures and performed a graded incremental maximal exercise test on a treadmill. During the exercise cardio-respiratory responses were measured continuously to allow determination of the ventilatory threshold (VT), heart rate (HR), and oxygen uptake (VO2). Furthermore, at rest before the exercise began, and after exercise blood samples were collected to allow measurement of: acid-base balance parameters, lactate, serum sex hormone levels (testosterone [T], progesterone [Prg], estradiol [E2], LH, FSH and prolactin [Prl] and glucostatic hormone levels (insulin [I], growth hormone [hGH] and cortisol [C]). Results indicated the subjects exercise to maximal levels and handball players had a slightly greater capacity. Significant differences were seen in the sex and glucostatic hormonal responses within and between the athletic groups. The findings suggest that there is an individually differentiated adaptation of the endocrine systems to maximal exercise within the groups. The reason for this differentiated adaptation could be due: (a) to the discrepancy in training volume between the athletic groups and/or, (b) a difference in the character to the types of training performed by athletes.